Mammadova, Masuma - (:unkn) unknown (My University, 2025)
Masuma Huseyn gizi Mammadova was born in 1951. In 1973, she graduated from the Faculty of Mechanics and Mathematics of Azerbaijan State University (Baku State University). In 1973-1977, she worked as a junior research worker in the Department of “Automation and Modeling of Petrochemical Processes” of the Institute of Petrochemical Processes of the Azerbaijan Academy of Sciences. In 1977-1980, she studied at the purposeful postgraduate course of the Institute of Cybernetics of the Ukrainian Academy of Sciences (Kiev city). In 1983, she defended her candidate's dissertation on the topic “Automated selection and inclusion of lexicon into the information-search thesaurus based on the analysis of terminological dictionaries” at the All-Union Institute of Scientific and Technical Information of the USSR Academy of Sciences (Moscow city) and received the degree of Candidate of Technical Sciences. In 1981-1987, she wored as a research worker in the “Applied Linguistics” department of the Institute of Linguistics of the Azerbaijan Academy of Sciences, where he studied the problems of automatic processing of natural languages, which is one of the main directions of artificial intelligence. In 1987, she was transferred to the Department of Automated Control Systems of the Azerbaijan Academy of Sciences (since 1997, it has been called the Information and Communication Science Center, and since 2002, it has been called the Institute of Information Technologies) and worked as an engineer and group leader. Since 1993, he has been working here as the head of the department. In 1996, she received the scientific title of senior research worker. In 1999, she defended his doctoral dissertation on the topic “Fundamentals of fuzzy relational structured knowledge processing technology and some of its applications” at Baku State University, specialty 05.13.14 “Special-purpose systems, data processing and management”, is a Doctor of Technical Sciences. In 2001-2013, she worked as the director of the Scientific Research and Training Center for Labor and Social Problems of the Ministry of Labor and Social Protection of the Population. In 2010, she received the academic title of professor. In 2017, she was elected a corresponding member of ANAS in the specialty “Informatics”.